Open Platform Concept for Blockchain-Enabled Crowdsourcing of Technology Development and Supply Chains - Ducrée, Jens; Gravitt, Max; Walshe, Ray; Bartling, Sönke; Etzrodt, Martin; Harrington, Tomás (Frontiers in Blockchain, 2020)
We outline the concept of an open technology platform which builds upon a publicly accessible library of fluidic designs, manufacturing processes and experimental characterisation, as well as virtualisation by a ‘digital twin”. Backed by the rapidly emerging Web3 technology “Blockchain”, we significantly extend traditional approaches to effectively incentivise broader participation by an interdisciplinary ‘value network’ of diverse players. Ranging from skilled individuals and more established research institutions to companies with their infrastructures, equipment and services, the novel platform approach enables all stakeholders to jointly contribute to value creation along more decentralised supply chain designs. Blockchain-enabled “Wisdom of the Crowds” and “Skin in the game” mechanisms secure “trust” and transparency between participants. Prediction markets are created for guiding decision making, planning and allocation of funding; competitive parallelisation of work and its validation from independent participants substantially enhances quality, credibility and speed of project outcomes along the entire path from RTD, fabrication and testing to eventual commercialisation. This novel, Blockchain-backed concept can be led by a corporation, academic entity, a loosely organised group, or even a Decentralised Autonomous Organisation (DAO). The proposed strategy is particularly attractive for highly interdisciplinary fields like Lab-on-a-Chip systems in the context of manifold applications in the Life Sciences. Rather than engaging in all sub-disciplines themselves, many smaller, highly innovative actors can focus on strengthening the product component distinguishing their unique selling point (USP). In this effort, system integrators access underlying commons like fluidic design, manufacture, instrumentation and software from a more resilient and diversified supply chain.